Oficinas, empleados y recaudación: el papel de la Hacienda Pública en la organización territorial de Guatemala (1826-1850) - Sarazúa Pérez, Juan Carlos (Revista de historia., 2014)
The article discusses some points about the State Treasury in Guatemala and the role played by it in the process of revenue collection. To do this, we present some figures on the number of staff and the role of departmental revenues. From this we can analyze the difficulties faced by officials to collect the resources outside the central region. Finally, it suggests the political role of the financial administration in the departments as arena of conflict.